Effects of medication procurement reforms and extended prescription duration on medication coverage for hypertension in India’s public health system: a modelling study - Kunihiro Matsushita; Andrew E Moran; Matti Marklund; Prabhdeep Kaur; Lawrence J Appel; T Joseph Mattingly; Swagata Kumar Sahoo (BMJ Public Health)
Objectives To estimate the effects of procurement reforms and extended prescription duration on medication coverage for hypertension in India’s public health system.Design Simulation study incorporating data from governmental medication price lists, prescription pattern analyses, and market sales surveys.Setting Simulated hypothetical public healthcare facility in India treating 1000 patients with hypertension.Participants Patients with medication-treated hypertension.Interventions (1) Focused procurement by reducing antihypertensive medication classes from 5 to 3 and selecting one medication within class; (2) Increased use of single-pill combinations (SPC) and (3) Only SPC dispensation. The base scenario consisted of procurement of multiple medications across classes, 1-month prescription duration and no use of SPC. We repeated all scenarios with extended prescription duration (3 months vs 1 month).Main outcome measures Medication coverage is defined as the maximum number of patients with adequate medication without exceeding the base scenario budget.Results With 1-month prescriptions, focused procurement alone was estimated to increase medication coverage by 17.8% (95% uncertainty interval: 16.2%; 19.6%) compared with the base scenario. Medication coverage improved by 3.6% (2.8%; 4.4%) with increased SPC use and by 10.3% (8.3%; 12.3%) with only SPC dispensation. Combining focused procurement and increased SPC use increased medication coverage by 20.2% (18.3%; 22.1%). When the prescription duration was extended to 3 months, the medication coverage was further increased by ~40% (eg, net improvement of ~60% with focused procurement, increased SPC use and 3-month prescriptions vs the base scenario).Conclusions With a fixed budget for medication procurement and dispensation, the combination of focused procurement, increased SPC use and extended prescription periods could substantially increase the number of patients who receive hypertension medications in India’s public health system. Our study highlights the benefits of implementing these reforms to scale up medication coverage for hypertension in India and potentially elsewhere.